Are Bangladeshi healthcare facilities prepared to provide antenatal care services? Evidence from two nationally representative surveys. - Shariful Hakim; Muhammad Abdul Baker Chowdhury; Zobayer Ahmed; Md Jamal Uddin (Public Library of Science (PLoS), 2022)
Identifying high-risk pregnancies through antenatal care (ANC) is considered the cornerstone to eliminating child deaths and improving maternal health globally. Understanding the factors that influence a healthcare facility's (HCF) preparedness to provide ANC service is essential for assisting maternal and newborn health system progress. We aimed to evaluate the preparedness of HCFs to offer ANC services among childbearing women in Bangladesh and investigate the facility characteristics linked to the preparedness. The data for this study came from two waves of the Bangladesh Health Facilities Survey (BHFS), conducted in 2014 and 2017 using a stratified random sample of facilities. The study samples were 1,508 and 1,506 HCFs from the 2014 and 2017 BHFS, respectively. The outcome variable "ANC services preparedness" was calculated as an index score using a group of tracer indicators. Multinomial logistic regression models were used to identify the significant correlates of ANC service preparedness. We found that private hospitals had a lower chance of having high preparedness than district and upazila public facilities in 2014 (RRR = 0.04, 95% CI: 0.01-0.22, p-value = <0.001) and 2017 (RRR = 0.23, 95% CI: 0.07-0.74, p-value = 0.01), respectively. HCFs from the Khulna division had a 2.84 (RRR = 2.84, CI: 1.25-6.43, p-value = 0.01) and 3.51 (RRR = 3.51, CI: 1.49-8.27, p-value = <0.001) higher likelihood of having medium and high preparedness, respectively, for ANC service compared to the facilities in the Dhaka division in 2017. The facilities that had a medium infection prevention score were 3.10 times (RRR = 3.10, 95% CI: 1.65-5.82; p-value = <0.001) and 1.89 times (RRR = 1.89, 95% CI: 1.09-3.26, p-value = 0.02) more likely to have high preparedness compared to those facilities that had a low infection prevention score in 2014 and 2017 respectively. Facilities without visual aids for client education on pregnancy and ANC were less likely to have high (RRR = 0.29, 95% CI: 0.16-0.53, p-value = <0.001) and (RRR = 0.55, 95% CI: 0.30-0.99, p-value = 0.04) preparedness, respectively, than those with visual aids for client education on pregnancy and ANC in both the surveys. At all two survey time points, facilities that did not maintain individual client cards or records for ANC clients were less likely to have high (RRR = 0.53, 95% CI: 0.31-.92, p-value = 0.02) and (RRR = 0.41, 95% CI: 0.25-0.66, p-value = <0.001) preparedness, respectively, compared to their counterparts. We conclude that most facilities lack adequate indicators for ANC service preparedness. To improve the readiness of ANC services, government authorities could focus on union-level facilities, community clinics, private facilities, and administrative divisions. They could also make sure that infection control items are available, maintain individual client cards or records for ANC clients, and also ensure ANC clients have access to visual aids.